Association of Acute Hyperglycemia and Diabetes Mellitus with Amount of Platelets Derived Microparticles During Acute Myocardial Infarction - Indana, Hana Anindya; Puspitawati, Ira; Mayasari, Dyah Samti; Hartopo, Anggoro Budi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objectives. This research aims to investigate whether there is an association between acute hyperglycemia and diabetes mellitus and the amount of circulating platelet-derived microparticles (PDMPs) during acute myocardial infarction (AMI) initial episode. Methodology. This was a cross-sectional study. Subjects were AMI patients underwent hospitalization. Demography and clinical data were obtained from hospital records. Diabetes mellitus was defined from history of disease, antidiabetic use and/or level of HbA1C ≥6.5%. Levels of HbA1c, admission random and fasting blood glucose levels were measured in hospital laboratory. The PDMPs was measured by flow-cytometry method, by tagging with CD-41 FITC and CD-62 PE markers and threshold size of <1 µm, from venous blood. The circulating PDMPs amount was compared according to glucometabolic state, namely acute hyperglycemia (admission random glucose ≥200 mg/dL and fasting glucose ≥140 mg/dL) and diabetes mellitus. The comparative analysis between group was conducted with Student T tests or Mann-Whitney tests, where applicable. Results. A total of 108 subjects were included and their data analyzed. Circulating PDMPs amount was significantly lower in subjects with admission random glucose ≥200 mg/dL as compared to those with below level (median (interquartile range (IQR)): 2,710.0 (718.0-8,167.0) count/mL vs. 4,452.0 (2,128.5-14,499.8) count/mL, p=0.05) and in subjects with fasting glucose ≥140 mg/dL as compared to those with below level (median (IQR): 2,382.0 (779.0-6,619.0) count/mL vs. 5,972.0 (2,345.7-14,781.3) count/mL, p=0.006). Circulating PDMPs amount was also significantly lower in diabetes mellitus as compared to non diabetic (median (IQR): 2,655.0 (840.0-5,821.0) count/mL vs. 4,562.0 (2,128.5-15,055.8) count/mL; p=0.007). Conclusion. Acute hyperglycemia and diabetes mellitus significantly associated with lower amount of circulating PDMPs during the initial episode of AMI.